2021
DOI: 10.2196/preprints.28874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile Diary App Versus Paper-Based Diary Cards for Patients With Borderline Personality Disorder: Economic Evaluation (Preprint)

Abstract: BACKGROUND The use of mobile diary applications (apps) in dialectical behaviour therapy (DBT) could entail several positive consequences, such as allowing therapists to follow their patients during treatment. OBJECTIVE The objective of this study was to examine the costs and consequences of using a mobile diary app compared to paper-based diary cards in DBT treatment for patients with borderlin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Others apps have incorporated behavioral interventions such as a diary as an adjunct to DBT treatment (77). In the same line, Schiffler et al have shown the implementation of a Mobile DBT App for young adults (aged 18 to 23 years) with a focus on suicidality and NSSI, in a natural setting, without showing effectiveness results (78).…”
Section: Discussionmentioning
confidence: 99%
“…Others apps have incorporated behavioral interventions such as a diary as an adjunct to DBT treatment (77). In the same line, Schiffler et al have shown the implementation of a Mobile DBT App for young adults (aged 18 to 23 years) with a focus on suicidality and NSSI, in a natural setting, without showing effectiveness results (78).…”
Section: Discussionmentioning
confidence: 99%